Perceived Quality of Nursing Care Among Cancer Patients Attending Machakos Level Five Hospital, Machakos County, Kenya - Hellen W. Wanjau; Lister Onsongo; Elizabeth Ambani (Journal of Medicine, Nursing and Public health, 2026)
This study sought to determine the perceived quality of nursing care among cancer patients at Machakos Level 5 Hospital in Machakos County, Kenya. This was an analytical cross-sectional inquiry conducted among adult patients with cancer at Machakos Level 5 Hospital. A total of 161 patients receiving treatment for varied forms of cancer in the hospital’s oncology unit were targeted. The respondents were selected using a simple random sampling approach. They filled out a questionnaire that included the QONCS scale. It was pre-tested among 16 adult patients with cancer at the Makueni County Referral Hospital. The QONCS is a validated tool and was therefore not part of the pretested study tool. The data were scrutinized using various explanatory metrics, including proportions, occurrence rates/numbers, averages, and measures of normal variation. Further, the variables under scrutiny were linked to patients’ assessments of the quality of oncology nursing care at Machakos Level 5 Hospital, using Fisher’s exact test at a 95% confidence level. SPSS version 25.0 was applied in the analysis. From the findings, the majority (96.6%, n = 143) rated the quality of nursing care at Machakos Level 5 Hospital as good, as indicated by total QONCS scores ranging from 129 to 170. The characteristics of acceptable oncology care by the nurses, as per the respondents, were feeling affirmed and validated (mean = 4.62, SD = 0.376); feeling valued (mean = 4.62, SD = 0.452); being cared for spiritually (mean = 3.40, SD = 0.759); sense of belonging (mean = 4.58, SD = 0.488) and respectful interactions (mean = 4.68, SD = 0.379). When supported and confirmed, the participants agreed that the nurses were emotionally supportive (97.3%) and responded promptly to their questions and concerns (98.6%). Regarding being valued, they agreed they were adequately cared for by the nurses (98%) and that the nurses were caring and understanding (98%). On a sense of belonging, they concurred that nurses acknowledged the importance of their family’s presence (95.9%). The study concluded that the nurses’ care was satisfactory, as they felt affirmed, validated, well-integrated, cherished, and respected, though divine care needed improvement. The study recommends ongoing efforts by healthcare workers and hospital management to maintain the reported high level of oncology therapy provided by nurses at the hospital.